The Influence of Work-life Balance and Perceived Organizational Support on Organizational Citizenship Behavior with Organizational Commitment as A Mediating Variable - Herni Justiana Astuti; Luthfi Arie Widzayanto; Eko Hariyanto; Fatmah Bagis (Universitas Negeri Semarang, 2024)
This study examines the effect of work-life balance and perceived organizational support on the Organizational Citizenship Behavior of nurses at RSI Muhammadiyah Tegal with organizational commitment as a mediator. This quantitative study uses primary data taken by distributing questionnaires via Google Forms. The population of this study was 231 nurses using purposive sampling techniques with the criteria of permanent nurses and a minimum work period of 1 year. Respondents who met the criteria numbered 155 people with a response rate of 116 people or 74.8 of the total population that met the criteria. The analysis tool used in this study was SEM-PLS 3. The findings of the study indicate that work-life balance and organizational commitment have a positive effect on Organizational Citizenship Behavior, inversely proportional to perceived organizational support which does not affect Organizational Citizenship Behavior, as well asorganizational commitment mediate the influence of work-life balance and perceived organizational support on Organizational Citizenship Behavior.